Malignant endometriosis-associated ovarian and extraovarian neoplasia (review of literature) - Kh. B. Kotiv; T. V. Gorodnova; O. E. Lavrinovich; I. V. Berlev (ABV-press, 2023)
Malignant transformation of endometrioid heterotopias develops in 0.7-2.5 % of cases; 75 % of cases have an ovarian localisation and 25 % an extraovarian one. As it has been suggested that malignant endometriosis-associated neoplasia (MEAN) is developed in foci of atypical endometriosis. The review describes the mechanisms of carcinogenesis, the clinical and morphological features of the disease, and the principles of therapy. MEAN usually occur in younger women, are detected at stages I-II, and are mostly represented by clear cell and endometrioid carcinomas, but rare histological types have also been described. CTNNB1, PTEN, PIK3CA and ARID1A mutations are often detected in MEAN. The treatment of MEAN is not standardised, there are no prospective randomized trials assessing treatment. Patients with ovarian MEAN receive therapy similar to epithelial ovarian cancer. Patients with extraovarian localisation represent a subgroup that of patients that may require a personalised approach.